2013
DOI: 10.2218/ijdc.v8i1.242
|View full text |Cite
|
Sign up to set email alerts
|

Competencies Required for Digital Curation: An Analysis of Job Advertisements

Abstract: With digital curation’s increasingly important role in the fast-paced and data-intensive information environment, there is a need to identify a set of competencies for professionals in this growing field. As part of a curriculum development project funded by the U.S. Institute of Museum and Library Services, a total of 173 job advertisements posted between October 2011 and April 2012 were collected from various sources to take into account varying types of professionals in the field of digital curation across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 18 publications
2
31
0
4
Order By: Relevance
“…They noted that responsibilities included institutional repository work, new publishing models, open access, copyright and authors' rights, and compliance with National Institute of Health (NIH) public access mandates (p. 274). Kim, Warga, and Moen (2013) looked at 173 job advertisements related to digital curation between October 2011 and April 2012 and concluded that the field "currently intersects with a variety of problems and domains from cultural heritage collections to eScience and data science" (p. 67). Detmering and Sproles (2012) determined scholarly communication to be a duty in 7.3% of the listings they studied and noted that "while not pervasive, scholarly communication emerged as another significant trend, particularly in science subject specialist positions.…”
Section: Job Ads For Scholarly Communication Librariansmentioning
confidence: 99%
“…They noted that responsibilities included institutional repository work, new publishing models, open access, copyright and authors' rights, and compliance with National Institute of Health (NIH) public access mandates (p. 274). Kim, Warga, and Moen (2013) looked at 173 job advertisements related to digital curation between October 2011 and April 2012 and concluded that the field "currently intersects with a variety of problems and domains from cultural heritage collections to eScience and data science" (p. 67). Detmering and Sproles (2012) determined scholarly communication to be a duty in 7.3% of the listings they studied and noted that "while not pervasive, scholarly communication emerged as another significant trend, particularly in science subject specialist positions.…”
Section: Job Ads For Scholarly Communication Librariansmentioning
confidence: 99%
“…First and foremost, it is well suited for this research inquiry. Analysis of job advertisements has been one of the two conventional approaches used for assessing and identifying skill sets required of an occupation (e.g., Ahsan et al, 2013;Harper, 2013;Hoffman & Bresciani, 2012;Kim et al, 2013;Marion, 2001;Marion et al, 2005;Park et al, 2009). The other conventional approach is to conduct surveys on a targeted population.…”
Section: Methodsmentioning
confidence: 99%
“…These included some of those Kim, Warga, Moen (2013) analysed in job advertisements for Digital Curation posts. Previous IT knowledge gained from projects such as website development, the Integrated Library System and database development were a plus for the staff.…”
Section: Innovative Solutions: Capacity Buildingmentioning
confidence: 99%